Target prioritization of novel substituted 5-aryl-2-oxo-/thioxo-2, 3-dihydro-1H-benzo[6, 7]chromeno[2, 3-d]pyrimidine-4, 6, 11(5H)-triones as anticancer agents using in-silico approach. Issue 5 (23rd March 2020) - Bhayye, Sagar S.; Brahmachari, Goutam; Nayek, Nayana; Roy, Sujata; Roy, Kunal
Abstract: Cancer is a multi-origin collection of diseases attributed by abnormal and uncontrolled cell growth spread from origin to other parts of body eventually leading to death. After decades of research, anticancer drug therapy is still very much limited to inhibiting growth and controlling the spread of tumour cells. Finding novel molecular targets and drug candidates using assimilation of experimental and computational approaches is among the recent strategies adopted by researchers to speed up the anticancer drug discovery process. In present study, synthesis of 40 novel substituted 5-aryl-2-oxo-/thioxo-2, 3-dihydro-1 H -benzo[6, 7]chromeno[2, 3- d ]pyrimidine-4, 6, 11(5 H )-triones has been accomplished followed by molecular target identification using different in silico approaches. The target prioritization methodology involved identification and selection of targets, molecular docking followed by molecular dynamic simulation and determination of binding free energy using MM-GBSA technique. Systematic and stepwise virtual screening of biological targets lead to identification of B-cell lymphoma 6 protein (BCL6), lysine-specific histone demethylase 1 A (LSD1), nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB P65) and poly (ADP-ribose) polymerase 1 (PARP1) as suitable anticancer targets for the set of synthesized compounds. Communicated by Ramaswamy H. Sarma